Peripheral Hemangioma of Maxillary Gingiva - A Case Report - Chaudhary Arati; Nivaskar Vilas (Wolters Kluwer Medknow Publications, 2006)
Hemangiomas of the jaw bones are rare benign lesions characterized by proliferation of the blood vessels. Peripheral hemangiomas that involve the soft tissue are more common in the mandible than in the maxilla. A case of peripheral vascular hemangioma in a young female patient which shows diversity in the site of occurrence is reported along with the latest investigation procedure that was employed for the diagnosis and treatment planning of maxillo-facial hemangiomas.